HUBUNGAN ANTARA MODAL SOSIAL DENGAN PELAKSANAAN GERAKAN SATU RUMAH SATU JUMANTIK DI DUSUN MEJING LOR AMBARKETAWANG GAMPING SLEMAN - Tri Wahyuni Sukesi; Arkana Januarti (Universitas Ahmad Dahlan, 2021)
Background : Dengue Hemorrhagic Fever (DHF) is still the main problem in Indonesia. Dengue disease control is to create individuals and communities who are independent in preventing and protecting themselves from dengue transmission through the optimization of 3M Plus PSN activities in addition to increasing public access to quality health services. One of the Dengue Control Missions is to promote aspects of empowerment and community participation as well as multi-sector partnerships.Community empowerment in controlling DHF requires strong social capital to be able to foster mutual.t rust in cooperation, participation, mutual trust and prevailing normsMosquito breeding activities must be carried out in every house, public place and institution by the larvae monitor (Jumantik). To get optimal results, the Jumantik must be formed starting from each house by designating one of the family members as the jumantik (Gerakan 1 Rumah 1 Jumantik)Method : This research is an analytic observational research with crossectional research design that is studying the dynamics of the correlation between risk factors between social capital independent variables with the dependent variable in this study the implementation of Gerakan Satu Rumah Satu Jumantik. The population in this study entire houses in Mejing Lor Ambarketawang Gamping Sleman. Samples were taken using total sampling technique in which samples using secondary data. Data was analysed with uji chi square of Software Statistic.Result : Based on the research that has been done, the correlation coefficient between social capital and the implementation Gerakan Satu Rumah Satu Jumantik is obtained, with the significance value on the results showing (p = 0,000 <0.05) which indicates a correlation. between social capital and the implementation of Gerakan Satu Rumah Satu Jumantik in the Mejing Lor Village, Ambarketawang Gamping. While the analysis obtained RP 5.406 > 1 with Confident Interval (2.716 -10.752) which means that respondents with bad social capital are more likely to implement the Gerakan Satu Rumah Satu Jumantik in the Mejing Lor Village, Ambarketawang Gamping is not good..Conclusions :There is a Correlation between Social Capital and the Implementation Gerakan Satu Rumah Satu Jumantik in the Mejing Lor Village, Ambarketawang Gamping